THE READER INTERPRETATION OF DEATH'S CONCEPT 'BECAUSE I COULD NOT STOP FOR DEATH' POEM BY DICKINSON - Titis Salsa Firdausiah; Neng Ita Izmi Habibah; Wulan Agustin; Thesa Izfadillah (Fakultas Ilmu Budaya and LPPM Universitas Sebelas April, 2025)
This study examines how readers in the modern era see death in Emily Dickinson's poem Because I Could Not Stop for Death. The study collected input from readers with varying backgrounds using reader response methods and investigated how various points of view affect how the symbolism of death is understood. The findings emphasize the significance of emotional and cultural circumstances in meaning construction by demonstrating how readers' opinions are strongly impacted by their own experiences. This study expands our understanding of the dynamic interaction between literary texts and readers.